Analisis Pengaruh Inflasi Terhadap Perekonomian Regional di Provinsi Papua Tahun 2015-2024 - Anderias Seran; Yundy Hafizrianda (Universitas Cenderawasih, 2026)
This study aims to analyze the inflation trend in Papua Province during the 2014-2023 period, explain the development of economic growth, and examine the effect of inflation on regional economic growth in Papua Province. The research method used is a quantitative approach with secondary time series data obtained from the Central Statistics Agency (BPS) of Papua Province and Bank Indonesia. The analysis was conducted through classical assumption tests (normality, multicollinearity, and autocorrelation), Pearson correlation test, and simple regression using the log-log elasticity model to measure the magnitude of inflation's effect on Gross Regional Domestic Product (GRDP) at constant prices. The results show that inflation in Papua Province during the 2014-2023 period experienced fairly high fluctuations, with the highest peak occurring in 2018 at 6.54 percent, while economic growth contracted by minus 1.10 percent in 2020 due to the COVID-19 pandemic before recovering in subsequent years. The regression analysis proves that inflation has a negative and significant effect on economic growth in Papua Province, with a regression coefficient of -1.154 and a significance value of 0.000, meaning that every 1 percent increase in inflation will reduce economic growth by 1.154 percent. The coefficient of determination (R Square) value of 0.284 indicates that inflation explains 28.4 percent of the variation in economic growth, while the remaining is influenced by other variables outside the model. Keywords: Inflation, Economic Growth, GRDP, Papua Province, Log-Log Regression